The Effectiveness of Online Learning in Pandemic Times to Face the Covid-19 Pandemic - Suprianto Suprianto; Sulaeman Sulaeman; Juliati Juliati; Aisyah Aisyah (Budapest International Research and Critics University, 2022)
The corona virus has made all the routines of the world of education ineffective. As is the case with this research, the goal is to find out the effectiveness of online learning during the pandemic to deal with the covid-19 pandemic among students. The method in this study uses a descriptive method with a qualitative approach to analyze a phenomenon to be studied through the support of a literature study so as to strengthen the results of the research obtained in making conclusions this is caused by boredom and boredom repeatedly so that it reaches a saturation point. In addition, the material that students are able to absorb is less than half, coupled with the ability of lecturers and. The results of this study are continuous online learning for students is very ineffective, students in using the internet which is still low. Thus, online learning is considered quite effective when it is only done from time to time, not continuously for 1 semester. Each semester there are approximately 10 courses that are taught with a total of 15 meetings so that in total a student has to face his computer screen more or less. In the future, online learning should only be carried out under certain conditions that do not allow face-to-face meetings, such as a natural disaster and coupled with an increase in the professionalism of the teaching staff in the use of various online applications so that learning does not become boring and boring. Thus, online learning is considered quite effective when it is only done from time to time, not continuously for 1 semester. Each semester there are approximately 10 courses that are taught with a total of 15 meetings so that in total a student has to face his computer screen more or less. In the future, online learning should only be carried out under certain conditions that do not allow face-to-face meetings, such as a natural disaster and coupled with an increase in the professionalism of the teaching staff in the use of various online applications so that learning does not become boring and boring. Thus, online learning is considered quite effective when it is only done from time to time, not continuously for 1 semester. Each semester there are approximately 10 courses that are taught with a total of 15 meetings so that in total a student has to face his computer screen more or less. In the future, online learning should only be carried out under certain conditions that do not allow face-to-face meetings, such as a natural disaster and coupled with an increase in the professionalism of the teaching staff in the use of various online applications so that learning does not become boring and boring.